The impact of crystal size and temperature on the adsorption-induced flexibility of the Zr-based metal–organic framework DUT-98 - Krause, Simon; Bon, Volodymyr; Du, Hongchu; Dunin-Borkowski, Rafal E.; Stoeck, Ulrich; Senkovska, Irena; Kaskel, Stefan (Beilstein Journal of Nanotechnology, 2019)
In this contribution we analyze the influence of adsorption cycling, crystal size, and temperature on the switching behavior of the flexible Zr-based metal–organic framework DUT-98. We observe a shift in the gate-opening pressure upon cycling of adsorption experiments for micrometer-sized crystals and assign this to a fragmentation of the crystals. In a series of samples, the average crystal size of DUT-98 crystals was varied from 120 µm to 50 nm and the obtained solids were characterized by X-ray diffraction, infrared spectroscopy, as well as scanning and transmission electron microscopy. We analyzed the adsorption behavior by nitrogen and water adsorption at 77 K and 298 K, respectively, and show that adsorption-induced flexibility is only observed for micrometer-sized crystals. Nanometer-sized crystals were found to exhibit reversible type I adsorption behavior upon adsorption of nitrogen and exhibit a crystal-size-dependent steep water uptake of up to 20 mmol g−1 at 0.5 p/p0 with potential for water harvesting and heat pump applications. We furthermore investigate the temperature-induced structural transition by in situ powder X-ray diffraction. At temperatures beyond 110 °C, the open-pore state of the nanometer-sized DUT-98 crystals is found to irreversibly transform to a closed-pore state. The connection of crystal fragmentation upon adsorption cycling and the crystal size dependence of the adsorption-induced flexibility is an important finding for evaluation of these materials in future adsorption-based applications. This work thus extends the limited amount of studies on crystal size effects in flexible MOFs and hopefully motivates further investigations in this field.
Keywords: crystal engineering; crystal size; flexible metal–organic frameworks; MOFs; water adsorption

(untitled) - Hönicke, I. M.; Senkovska, I.; Bon, V.; Baburin, I. A.; Bönisch, N.; Raschke, S.; Evans, J. D.; Kaskel, S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Li, H.; Wang, K.; Sun, Y.; Lollar, C. T.; Li, J.; Zhou, H.-C. (Mater. Today, 2018)

(untitled) - Krause, S.; Bon, V.; Senkovska, I.; Stoeck, U.; Wallacher, D.; Többens, D. M.; Zander, S.; Pillai, R. S.; Maurin, G.; Coudert, F.-X.; Kaskel, S. (Nature, 2016)

(untitled) - Mason, J. A.; Oktawiec, J.; Taylor, M. K.; Hudson, M. R.; Rodriguez, J.; Bachman, J. E.; Gonzalez, M. I.; Cervellino, A.; Guagliardi, A.; Brown, C. M.; Llewellyn, P. L.; Masciocchi, N.; et al. (Nature, 2015)

(untitled) - Chang, Z.; Yang, D.-H.; Xu, J.; Hu, T.-L.; Bu, X.-H. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Zhang, X.; Zhang, Q.; Yue, D.; Zhang, J.; Wang, J.; Li, B.; Yang, Y.; Cui, Y.; Qian, G. (Small, 2018)

(untitled) - Biswas, S.; Ahnfeldt, T.; Stock, N. (Inorg. Chem., 2011)

(untitled) - Yot, P. G.; Yang, K.; Guillerm, V.; Ragon, F.; Dmitriev, V.; Parisiades, P.; Elkaïm, E.; Devic, T.; Horcajada, P.; Serre, C.; Stock, N.; Mowat, J. P. S.; et al. (Eur. J. Inorg. Chem., 2016)

(untitled) - Krause, S.; Bon, V.; Senkovska, I.; Többens, D. M.; Wallacher, D.; Pillai, R. S.; Maurin, G.; Kaskel, S. (Nat. Commun., 2018)

(untitled) - Tanaka, H.; Ohsaki, S.; Hiraide, S.; Yamamoto, D.; Watanabe, S.; Miyahara, M. T. (J. Phys. Chem. C, 2014)

(untitled) - Gallaba, D. H.; Albesa, A. G.; Migone, A. D. (J. Phys. Chem. C, 2016)

(untitled) - Tanaka, S.; Fujita, K.; Miyake, Y.; Miyamoto, M.; Hasegawa, Y.; Makino, T.; Van der Perre, S.; Cousin Saint Remi, J.; Van Assche, T.; Baron, G. V.; Denayer, J. F. M. (J. Phys. Chem. C, 2015)

(untitled) - Zhang, C.; Gee, J. A.; Sholl, D. S.; Lively, R. P. (J. Phys. Chem. C, 2014)

(untitled) - Yang, F.; Mu, H.; Wang, C.; Xiang, L.; Yao, K. X.; Liu, L.; Yang, Y.; Han, Y.; Li, Y.; Pan, Y. (Chem. Mater., 2018)

(untitled) - Cheng, X.; Zhang, A.; Hou, K.; Liu, M.; Wang, Y.; Song, C.; Zhang, G.; Guo, X. (Dalton Trans., 2013)

(untitled) - Kundu, T.; Wahiduzzaman, M.; Shah, B. B.; Maurin, G.; Zhao, D. (Angew. Chem., Int. Ed., 2019)

(untitled) - Kavoosi, N.; Bon, V.; Senkovska, I.; Krause, S.; Atzori, C.; Bonino, F.; Pallmann, J.; Paasch, S.; Brunner, E.; Kaskel, S. (Dalton Trans., 2017)

(untitled) - Miura, H.; Bon, V.; Senkovska, I.; Ehrling, S.; Watanabe, S.; Ohba, M.; Kaskel, S. (Dalton Trans., 2017)

(untitled) - Sakata, Y.; Furukawa, S.; Kondo, M.; Hirai, K.; Horike, N.; Takashima, Y.; Uehara, H.; Louvain, N.; Meilikhov, M.; Tsuruoka, T.; Isoda, S.; Kosaka, W.; et al. (Science, 2013)

(untitled) - Schaber, J.; Krause, S.; Paasch, S.; Senkovska, I.; Bon, V.; Többens, D. M.; Wallacher, D.; Kaskel, S.; Brunner, E. (J. Phys. Chem. C, 2017)

(untitled) - Férey, G.; Serre, C. (Chem. Soc. Rev., 2009)

(untitled) - Millange, F.; Serre, C.; Férey, G. (Chem. Commun., 2002)

(untitled) - Krause, S.; Bon, V.; Stoeck, U.; Senkovska, I.; Többens, D. M.; Wallacher, D.; Kaskel, S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Shi, Y.-X.; Li, W.-X.; Zhang, W.-H.; Lang, J.-P. (Inorg. Chem., 2018)

(untitled) - Su, J.; Yuan, S.; Wang, H.-Y.; Huang, L.; Ge, J.-Y.; Joseph, E.; Qin, J.; Cagin, T.; Zuo, J.-L.; Zhou, H.-C. (Nat. Commun., 2017)

(untitled) - Li, X.; Chen, X.; Jiang, F.; Chen, L.; Lu, S.; Chen, Q.; Wu, M.; Yuan, D.; Hong, M. (Chem. Commun., 2016)

(untitled) - Maji, T. K.; Mostafa, G.; Matsuda, R.; Kitagawa, S. (J. Am. Chem. Soc., 2005)

(untitled) - Tanaka, D.; Nakagawa, K.; Higuchi, M.; Horike, S.; Kubota, Y.; Kobayashi, T.; Takata, M.; Kitagawa, S. (Angew. Chem., Int. Ed., 2008)

(untitled) - Bon, V.; Kavoosi, N.; Senkovska, I.; Kaskel, S. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Schaate, A.; Roy, P.; Godt, A.; Lippke, J.; Waltz, F.; Wiebcke, M.; Behrens, P. (Chem. – Eur. J., 2011)

(untitled) - Morris, W.; Wang, S.; Cho, D.; Auyeung, E.; Li, P.; Farha, O. K.; Mirkin, C. A. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Hu, Z.; Castano, I.; Wang, S.; Wang, Y.; Peng, Y.; Qian, Y.; Chi, C.; Wang, X.; Zhao, D. (Cryst. Growth Des., 2016)

(untitled) - Zahn, G.; Schulze, H. A.; Lippke, J.; König, S.; Sazama, U.; Fröba, M.; Behrens, P. (Microporous Mesoporous Mater., 2015)

(untitled) - Bueken, B.; Van Velthoven, N.; Willhammar, T.; Stassin, T.; Stassen, I.; Keen, D. A.; Baron, G. V.; Denayer, J. F. M.; Ameloot, R.; Bals, S.; De Vos, D.; Bennett, T. D. (Chem. Sci., 2017)

(untitled) - Liu, L.; Zhang, J.; Fang, H.; Chen, L.; Su, C.-Y. (Chem. – Asian J., 2016)

(untitled) - Liu, L.; Chen, Z.; Wang, J.; Zhang, D.; Zhu, Y.; Ling, S.; Huang, K.-W.; Belmabkhout, Y.; Adil, K.; Zhang, Y.; Slater, B.; Eddaoudi, M.; et al. (Nat. Chem., 2019)

(untitled) - Øien, S.; Wragg, D.; Reinsch, H.; Svelle, S.; Bordiga, S.; Lamberti, C.; Lillerud, K. P. (Cryst. Growth Des., 2014)

(untitled) - Furukawa, H.; Gándara, F.; Zhang, Y.-B.; Jiang, J.; Queen, W. L.; Hudson, M. R.; Yaghi, O. M. (J. Am. Chem. Soc., 2014)

(untitled) - Kim, H.; Yang, S.; Rao, S. R.; Narayanan, S.; Kapustin, E. A.; Furukawa, H.; Umans, A. S.; Yaghi, O. M.; Wang, E. N. (Science, 2017)

(untitled) - Kim, H.; Rao, S. R.; Kapustin, E. A.; Zhao, L.; Yang, S.; Yaghi, O. M.; Wang, E. N. (Nat. Commun., 2018)

(untitled) - Kalmutzki, M. J.; Diercks, C. S.; Yaghi, O. M. (Adv. Mater. (Weinheim, Ger.), 2018)

(untitled) - Shivanna, M.; Yang, Q.-Y.; Bajpai, A.; Sen, S.; Hosono, N.; Kusaka, S.; Pham, T.; Forrest, K. A.; Space, B.; Kitagawa, S.; Zaworotko, M. J. (Sci. Adv., 2018)

(untitled) - Zheng, B.; Fu, F.; Wang, L. L.; Wang, J.; Du, L.; Du, H. (J. Phys. Chem. C, 2018)

(untitled) - Thornton, A. W.; Babarao, R.; Jain, A.; Trousselet, F.; Coudert, F.-X. (Dalton Trans., 2016)

(untitled) - Dissegna, S.; Vervoorts, P.; Hobday, C. L.; Düren, T.; Daisenberger, D.; Smith, A. J.; Fischer, R. A.; Kieslich, G. (J. Am. Chem. Soc., 2018)

(untitled) - Keupp, J.; Schmid, R. (ChemRxiv, 2019)